Regenerative agriculture. An innovative approach towards mitigation of climate change through multi-tier learning - Kniec, Wojciech (Eastern European Countryside, 2025)
The development of regenerative agriculture has been attracting particular attention from the scientific community for almost a decade, both from researchers in the agricultural sciences and the natural and social sciences, as well as from agro-technologists, ecologists, and agricultural consultants. Nothing is surprising about this. This is essentially a grassroots type of agricultural production which, on the one hand, is based on state-of-the-art agro-technical solutions (e.g. precision farming or modern forms of cultivation, sowing, etc.) while, on the other hand, making use of former cultivation and animal husbandry techniques stemming from the rural production system. This is further compounded by the latest ecological research revealing the interactions between plants and animals to avoid or drastically reduce the share of chemicals in agricultural production. Farmers engaged in this type of production group together in networks of cooperation and knowledge exchange, creating a social movement that is very interesting for social researchers.